(untitled) (International Journal of Applied Sciences and Biotechnology, 2013)
An experiment was conducted at the Seed Laboratory of the Department of Agronomy, Bangladesh Agricultural University, Mymensingh during the period from January to April 2012 to study the effect of hydropriming on field establishment of seedlings obtained from primed seeds of Boro rice cv. BRRI dhan29. Seeds were soaked in water for 0, 24, 30, 36, 42, 48, 54 and 60 hours. The incubation period was 30 hours at 35°C temperature. Seed quality viz. percent germination, mean germination time, vigor index, shoot length, root length, shoot dry weight and root dry weight of rice seedlings were measured. Plant population m-2 also recorded to understand the field establishment of primed seeds. It was observed that priming treatments had significant effect on germination and other growth parameters of rice seedlings. The highest germination, vigor index, population m-2, length of shoot and root and their weight were found at 15 and 30 DAS. The lowest mean germination time was observed from hydropriming of seeds with 30 hours soaking. On the contrary, no priming treatment showed the lowest germination, vigor index, population m-2, and the highest mean germination time. The study concludes that BRRI dhan29 rice seed could be primed for 30 hours as hydropriming improves germination and field establishment of rice seedlings of Boro rice cv. BRRI dhan29. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9102 Int J Appl Sci Biotechnol, Vol. 1(4): 220-223